2019
DOI: 10.3390/ijgi8050217
|View full text |Cite
|
Sign up to set email alerts
|

Why Shape Matters—On the Inherent Qualities of Geometric Shapes for Cartographic Representations

Abstract: All human communication involves the use of signs. By following a mutually shared set of signs and rules, meaning can be conveyed from one entity to another. Cartographic semiology provides such a theoretical framework, suggesting how to apply visual variables with respect to thematic content. However, semiotics does not address how the choice and composition of such visual variables may lead to different connotations, interpretations, or judgments. The research herein aimed to identify perceived similarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Such particular stimulus-affect correspondences are moreover supported by related empirical research on map symbols, which found that asymmetric star symbols were experienced as highly dynamic and of negative valence, whereas symmetric shapes were regarded as neutral or slightly positive and of rather static quality [44]. Related research further showed that point symbols may be experienced visually, associatively, and affectively [43]. Map topic-specific visualization preferences may therefore result due to either of these dimensions.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Such particular stimulus-affect correspondences are moreover supported by related empirical research on map symbols, which found that asymmetric star symbols were experienced as highly dynamic and of negative valence, whereas symmetric shapes were regarded as neutral or slightly positive and of rather static quality [44]. Related research further showed that point symbols may be experienced visually, associatively, and affectively [43]. Map topic-specific visualization preferences may therefore result due to either of these dimensions.…”
Section: Discussionmentioning
confidence: 62%
“…Empirical research, moreover, highlights a significant impact on map reading intuitiveness, judgments, and preferences towards maps based on how uncertainty is cartographically visualized [33,[39][40][41]. Empirical research on abstract map symbols further suggests a significant influence on detection speed in visual search tasks [42] as well as on associative and affective responses [43,44] based on symbol type.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Brychtova & Coltekin (2016) combine eye-tracking with traditional usability metrics to assess the effectiveness of visualisation and Nivala et al, (2003) explore field tests to identify, at an early stage of the project, preliminary design principles for maps in small displays. Klettner (2019) investigates shape proximities and cognitive relation in symbology, while Stone (2006) defines some guidelines for choosing colours. The main challenge of SIMILE app map view, using Chandler's (2002) words, "is changing the form of the signifier while keeping the same signified in order to generate different connotations".…”
Section: Previous Studies On Geovisualisationmentioning
confidence: 99%
“…While studying specific map types (such as earthquake maps and weather maps) allow us to observe specific patterns for the studied "visualization families", there are certain considerations at a fundamental level that would potentially apply to all visuospatial displays. In "Why Shape Matters-On the Inherent Qualities of Geometric Shapes for Cartographic Representations", Klettner (2019) [22] characterizes the strategies users apply when evaluating and comparing basic geometric shapes (which are included in all visuospatial displays). Klettner's study seeks to dive one level deeper into the crucial visual variable of shape, to see whether or not it is possible to separate types of shapes into discriminable categories.…”
Section: Cognition and 3d Representationmentioning
confidence: 99%